EVIL, ORIGINAL SIN, AND EVOLUTION - Pendergast, Richard J. (Heythrop journal, 2009)
This article has three sections. The first discusses the problem of evil; the second, the sins of both angels and men that originally introduced evil into the world; the third, a teleological theory of evolution that clarifies the relationship between the first two sections. At present there is a great deal of discussion about the nature of the evolutionary process. Some argue that ultimately it is a strictly random one. But it is quite impossible to prove scientifically that evolution is strictly random. From a Christian point of view the best way to view it is to see it not only as the result of divine intelligence, but also as due to a ferocious conflict between superhuman powers – the biblical angels and demons to whom God in the beginning gave the power to guide and develop his creation.